Antifilarial Activity of the Methanolic Extract of Indigofera tinctoria (Fabaceae) on Bovine Parasites (Onchocerca ochengi) - Enock Enock Rakwa; Benoît Bargui Koubala; Bertrand Ndou Mando; Mathieu Djongra; Francis Nveikoueing; Dieudonné Ndjonka (Journal of Parasitology Research)
Onchocerciasis is a major public health problem caused by Onchocerca volvulus parasite and transmitted to humans via black flies (simulium) bites. The control of onchocerciasis relies much on the use of the chemical drug ivermectin, which is only effective against microfilariae and has led to drug resistance. This study was carried out to assess the in vitro antifilarial activity of methanolic extract of Indigofera tinctoria and its most active fractions on adult male O. ochengi worm, the closest model to O. volvulus, after 48 h and 72 h of treatment. Worms’ viability was determined biochemically by MTT/formazan colorimetry assay. The promising plant extract’s acute and subacute oral toxicity were evaluated on both mice and rats. The result revealed a highest antifilarial activity of the methanolic extract (LC50=12.28 μg/mL) compared to ivermectin (LC50=26.50 μg/mL) after 72 h of treatment. Out of the eight (08), chromatographic fractions screened, only three (03) fractions (C, F, and G) revealed the highest anti-Onchocerca activity after 72 h of treatment. An oral administration of the plant extract at a single dose of 2000 mg/kg did not produce any toxicity in mice. After repeated daily administration of methanolic extract of I. tinctoria (250 mg/kg, 500 mg/kg, and 1000 mg/kg) for 28 days, no significant changes in body weight, biochemical, and haematological parameters was observed. Histopathological examination of organs did not reveal any sign of alteration. The phytochemical analysis of the methanolic extract of I. tinctoria revealed the presence of various phenolic compounds. Therefore, this study demonstrated the potential antifilarial activity of Indigofera tinctoria and offered an alternative to treating onchocerciasis. Moreover, further studies could be developed in promising new antifilarial sources of the isolated compound and in vivo antifilarial activity of Indigofera tinctoria in the animal model needs to be studied.